2023
DOI: 10.1002/jgm.3127
|View full text |Cite
|
Sign up to set email alerts
|

miR‐4286 promotes prostate cancer progression by targeting the expression of SALL1

Abstract: Background: Prostate cancer (PCa) is a serious health threat for humans worldwide.Recent studies have revealed that microRNAs are associated with the progression of human cancers, including PCa. However, no study has been performed aiming to investigate the role of microNA-4286 (miR-4286) on PCa.Methods: A quantitative reverse transcriptase-polymerase chain reaction was conducted to analyze the expression level of miR-4286 in PCa cells. The connection of miR-4286 and spalt like transcription factor 1 (SALL1) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 13 publications
(40 reference statements)
0
7
0
Order By: Relevance
“…Since the function of miRNAs are realized via modulating their target genes’ mRNA expression [ 26 ], we here conducted the bioinformatics analysis and verification experiment, and revealed that spalt like transcription factor 1 (SALL1) was one of the potential downstream target genes of miR-1243. The SALL1 is a member of Krüppel-associated box-containing zinc finger proteins (KRAB-ZFPs), and has been revealed to modulate the initiation and progression of human tumors [ 27 , 28 ]. SALL1 acted as a tumor suppressor gene in human glioma [ 27 ] and breast cancer ( Ma et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the function of miRNAs are realized via modulating their target genes’ mRNA expression [ 26 ], we here conducted the bioinformatics analysis and verification experiment, and revealed that spalt like transcription factor 1 (SALL1) was one of the potential downstream target genes of miR-1243. The SALL1 is a member of Krüppel-associated box-containing zinc finger proteins (KRAB-ZFPs), and has been revealed to modulate the initiation and progression of human tumors [ 27 , 28 ]. SALL1 acted as a tumor suppressor gene in human glioma [ 27 ] and breast cancer ( Ma et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…SALL1 acted as a tumor suppressor gene in human glioma [ 27 ] and breast cancer ( Ma et al, 2018 ). Further, miR-4286 may exert its tumor-promoting actions, in part, by downmodulating SALL1 in prostate cancer (PCa) [ 28 ]. Based on the above studies, we hypothesized that SALL1 may be partially required for circ_0043265 to exert its anti-oncogenic effect in TSCC.…”
Section: Discussionmentioning
confidence: 99%
“…To date, numerous non-coding RNAs have been demonstrated to have a crucial role in various types of cancer, including PCa (20). For example, miR-215-5p repressed the metastasis of PCa through targeting phosphoglycerate kinase 1 (21); miR-1272 reduced the migration and invasion of PCa by targeting huntingtin interaction protein 1 (22); and the inhibition of miR-4286 inhibited the proliferation and promoted the apoptosis of PCa by targeting spalt like transcription factor 1 (23). As for the role of miR-583 in PCa, to the best of our knowledge, only one meta-analysis report exists reporting its downregulation in recurrent PCa samples compared with non-recurrent cases (18).…”
Section: Discussionmentioning
confidence: 99%
“…In cancer, Sall1 has been found to be downregulated in breast cancer, glioblastoma ( 77 ), and myeloid leukemia, supporting its role as a tumor suppressor ( 76 ). In support of such a tumor suppressor role, Sall1 has been found to be a target of oncogenic miRNAs.…”
Section: Spalt-like Transcription Factormentioning
confidence: 98%